2014
DOI: 10.1371/journal.pone.0090008
|View full text |Cite
|
Sign up to set email alerts
|

The has-miR-526b Binding-Site rs8506G>A Polymorphism in the lincRNA-NR_024015 Exon Identified by GWASs Predispose to Non-Cardia Gastric Cancer Risk

Abstract: Gastric cancer including the cardia and non-cardia types is the second frequent cause of cancer-related deaths worldwide. A subset of non-cardia gastric cancer genetic susceptibility loci have been addressed among Asian through genome-wide association studies (GWASs). This study was to evaluate the effects of single nucleotide polymorphisms (SNPs) of long intergenic non-coding RNAs (lincRNAs) on non-cardia gastric cancer susceptibility in Chinese populations. We selected long intergenic noncoding RNAs (lincRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Luciferase report assay showed that the rs6976789 variant T allele influenced the binding ability of miR-148a. Similar research have been done in GC [33,34,35]. …”
Section: Discussionsupporting
confidence: 59%
“…Luciferase report assay showed that the rs6976789 variant T allele influenced the binding ability of miR-148a. Similar research have been done in GC [33,34,35]. …”
Section: Discussionsupporting
confidence: 59%
“…Until now, investigation into the role of hsa-miR-526b has been very limited. A recent genome-wide association study found that the hsa-miR-526b binding-site rs8506G > A polymorphism in the lincRNA-NR_024015 exon predisposes Chinese people to a higher risk of non-cardiac gastric cancer [32]. Hsa-miR-526b is identified as one of the pregnancy-associated miRNAs found in maternal plasma [33].…”
Section: Discussionmentioning
confidence: 99%
“…The rs13252298 and rs1456315 were associated with significantly decreased risks of CRC. Similarly, rs217727 AA in H19 and rs8506G > A in lincRNA‐NR_024015 are associated with increased risk of bladder cancer and non‐cardia gastric cancer, respectively.…”
Section: Lncrna Snps In Cancer Risk Predictionmentioning
confidence: 97%